2017
DOI: 10.1186/s12931-017-0536-7
|View full text |Cite
|
Sign up to set email alerts
|

Altered mTOR and Beclin-1 mediated autophagic activation during right ventricular remodeling in monocrotaline-induced pulmonary hypertension

Abstract: BackgroundRight ventricular structure and function is a major predictor of outcomes in pulmonary hypertension (PH), yet the underlying mechanisms remain poorly understood. Growing evidence suggests the importance of autophagy in cardiac remodeling; however, its dynamics in the process of right ventricle(RV) remodeling in PH has not been fully explored. We sought to study the time course of cardiomyocyte autophagy in the RV in PH and determine whether mammalian target of rapamycin (mTOR) and Beclin-1 hypoxia-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 56 publications
4
19
0
Order By: Relevance
“…Thus, decreased miR-26b, miR-204 and miR-497 were associated with the increased autophagy and cardiac hypertrophy. Previous studies also demonstrated that ULK1 and LC3B were activated during cardiac hypertrophy, and Beclin1 mediated autophagy was also enhanced during right ventricular remodeling (Huang et al, 2015;Deng et al, 2017;Zhang et al, 2019), supporting our finding that ULK1, LC3B, and Beclin1 were up-regulated in physiological LVH. Given LVH in response to endurance exercise is protective, the miRNA changes in physiological LVH is supposed to be adaptive and to promote moderate autophagy which is essential for physiological LVH.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, decreased miR-26b, miR-204 and miR-497 were associated with the increased autophagy and cardiac hypertrophy. Previous studies also demonstrated that ULK1 and LC3B were activated during cardiac hypertrophy, and Beclin1 mediated autophagy was also enhanced during right ventricular remodeling (Huang et al, 2015;Deng et al, 2017;Zhang et al, 2019), supporting our finding that ULK1, LC3B, and Beclin1 were up-regulated in physiological LVH. Given LVH in response to endurance exercise is protective, the miRNA changes in physiological LVH is supposed to be adaptive and to promote moderate autophagy which is essential for physiological LVH.…”
Section: Discussionsupporting
confidence: 91%
“…Conversely, in the AL group exposed to CH, increased mTOR activation and decreased AMPK activation showed an inverse regulation between the two kinases. Further support for our findings comes from reports demonstrating that the inhibition of mTOR under chronic hypobaric hypoxic conditions resulted in the prevention of RVH in an animal model (Paddenberg et al, 2007) and that increased AMPK activity and decreased mTOR activity attenuated RVH in pulmonary-artery-hypertensioninduced rats (Deng et al, 2017).…”
Section: Discussionsupporting
confidence: 80%
“…Indeed, mice with cardiac‐specific deletion of Ttg5 developed severe LV dilatation and cardiac dysfunction, with accumulation of misfolded proteins at the early stage after TAC and without cardiac functional compensation . Similarly, Deng et al found that induced autophagy was protective for the right ventricle in the compensatory phase after pulmonary hypertension. Hence, the presence of basal and even moderate autophagy at this early stage of cardiac remodelling is beneficial for retaining a normal myocardial structure.…”
Section: Discussionmentioning
confidence: 97%
“…Another interesting finding from this study was that during the decompensatory period, the excessive activation of autophagy was accompanied by the increased expression of HIF‐α, BNIP3 and beclin 1, which was barely seen in the early stage. Prior studies have suggested that the different roles of autophagy depend on the activation of different signalling pathways . Beclin 1 and BNIP3 serve as cross‐talk molecules between the autophagic and apoptotic pathways, which may contribute to the autophagy‐originated cardiac damage during this period.…”
Section: Discussionmentioning
confidence: 99%